Pemberdayaan Masyarakat dalam Mengelola Limbah Rumah Potong Hewan Berbasis Smart Farming Desa Candimulyo, Jombang : Pengabdian - Anang Rohmad Jatmiko; Asnun Parwanti; Junaedi; Machrus Ali; Ahmad Yusuf Andrian Putra; Ryo Setyawan (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The Community Partnership Program (PKM) was carried out by Universitas Darul Ulum Jombang in collaboration with Bank Santri (Integrated Independent Waste Bank) in Candimulyo Village, Jombang. The partner faces a major problem of cattle rumen waste from the local slaughterhouse, which causes pollution, foul odors, and health risks. To address this issue, the program introduced a smart farming approach through the installation of a compost sieving machine, an automatic fermentor for liquid organic fertilizer (LOF), and a Smart Sprinkle system for liquid fertilizer application. These technologies were integrated with digital business management and social media–based marketing strategies.The main achievements up to this reporting stage include: (1) initial installation of smart farming technology; (2) training on organic fertilizer production, business management, and digital marketing; (3) drafting of SOPs for production, management, and occupational health and safety; (4) an increase in organic fertilizer production capacity by approximately 25–30% compared to the initial condition; (5) development of the website banksantri.my.id integrated with social media; and (6) strengthening product identity under the brand INTAN (Idaman Tani Nusantara).This PKM program contributes to the achievement of SDG 2 (Zero Hunger) and SDG 12 (Responsible Consumption and Production), as well as supports the government’s Asta Cita agenda in promoting a green economy through innovation and community empowerment.